Neuroendocrine carcinoma of the rectum - González, Daniel; Rodríguez, Gustavo; Plazzotta, Cecilia; Rondán, Mariela; Ruso, Luis; Balboa, Oscar (Cirugía del Uruguay, 2003)
The paper deals with a neuro-endocrinous carcinoma of rectum, a highly aggressi ve histological variety of cancer rarely found in this topography- The patients was a 79-year-old woman carrying a TNM stage IV. The operation performed consisted of a low anterior oncological resection of rectum. Inmediate evolution showed rapid progression of lesion and the exploratory laparostomy performed 4 months later showed gastric infiltration thereby. It was therefore decided to proceed no further. In addition the paper contains an analysis of the various factors involved in prognosis of this condition.